2018
DOI: 10.3389/fmed.2018.00342
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute Transitional Journey: Caring for Orthopedic Surgery Patients in the United States

Abstract: As the geriatric population in the United States continues to age, there will be an increased demand for total hip and total knee arthroplasties (THAs and TKAs). Older patients tend to have more comorbidities and poorer health, and will require post-acute care (PAC) following discharge. The most utilized PAC facilities following THA and TKA are skilled nursing facilities (SNFs), in-patient rehabilitation facilities (IRFs), and home with home health care (HHC). Coordination of care between hospitals and PACs, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Clinical redesign understand, define, and improve clinical processes that underpin the patient journey across the continuum of care, promoting collaborative team-based care models and the adoption of emerging technologies to improve efficiency [ 45 , 46 ]. In the orthopedic journey, experiences transcend clinical and hospital environments, and patients may be suitable for early discharge to home with appropriate support services, including education for patients and caregivers, or may be discharged to inpatient rehabilitation facilities to allow for more advanced medical care [ 47 ]. During rehabilitation, design thinking contributes to improving individual’s ability to actively live a healthy lifestyle [ 48 ]; for example, to transform physical therapy into game play and art creation, gesture-based interactive platforms have been developed [ 49 ].…”
Section: Prototyping and Validation: The Path Towards The Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical redesign understand, define, and improve clinical processes that underpin the patient journey across the continuum of care, promoting collaborative team-based care models and the adoption of emerging technologies to improve efficiency [ 45 , 46 ]. In the orthopedic journey, experiences transcend clinical and hospital environments, and patients may be suitable for early discharge to home with appropriate support services, including education for patients and caregivers, or may be discharged to inpatient rehabilitation facilities to allow for more advanced medical care [ 47 ]. During rehabilitation, design thinking contributes to improving individual’s ability to actively live a healthy lifestyle [ 48 ]; for example, to transform physical therapy into game play and art creation, gesture-based interactive platforms have been developed [ 49 ].…”
Section: Prototyping and Validation: The Path Towards The Marketmentioning
confidence: 99%
“… Understanding the nature of problems : design, as the science of the artificial [ 58 ], is well-suited for approaching complex problems, yet it is of little use when solving well-defined problems. Design thinking initiatives are human-centered, such as designing for an aging population, that will be more functionally dependent [ 59 ], demanding initiatives to maintain the physical capacity [ 60 ], with greater probability of accessing healthcare services [ 47 ], considering the need for “social distancing” caused by the COVID-19 pandemic that complicates traditional care model for recovery after medical procedures that demand intensive physical therapies [ 37 ]. Moreover, to align current and future services, new models of care need to be developed, to ensure that the right care is delivered at the right time by the most appropriately trained health professional and at a reasonable cost [ 4 , 17 ].…”
Section: How To Innovate With Design Thinking?mentioning
confidence: 99%
“…For example, members of the care team, such as orthopedic surgeons who usually attend patients in the acute setting, usually do not have a physical presence in PAC facilities. 18 The majority of patients require some form of PAC after a hip fracture. 10 Postacute care may be delivered at home (including senior living centers and assisted living facilities) with physical therapists and nurses, in a skilled nursing facility or, in complicated cases, an inpatient rehabilitation hospital.…”
Section: Introductionmentioning
confidence: 99%
“…For example, members of the care team, such as orthopedic surgeons who usually attend patients in the acute setting, usually do not have a physical presence in PAC facilities. 18 …”
Section: Introductionmentioning
confidence: 99%
“…A review of literature on transitioning patients from the hospital post-TKA and post-THA found that home health patients had fewer complications compared with patients transferred to postacute facilities. 32 Haghverdian et al (2017) noted that a lack of continuity of PT during the transition from hospital to skilled nursing facility (SNF) led to reduced functionality, while Mallinson et al (2014) found that none of the types of postacute care (inpatient rehabilitation facilities [IRFs], SNFs, and HHC) exhibited an advantage over the other in terms of self-care and functionality when the total LOS in post-acute care (PAC) was controlled for. 33,34…”
Section: Introductionmentioning
confidence: 99%